2001
DOI: 10.1080/00365510151097700
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses and myocardial injury in coronary artery bypass grafting

Abstract: The results indicated that off-pump revascularization was associated with reduced cytokine responses and less severe myocardial injury. The degree of myocardial injury, as defined by CK-MB release, correlated with cytokine release. Intervention designed to reduce cytokine responses in cardiac surgery may be advantageous for patients with severe comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As a result of these changes, animals treated with ND demonstrated increased blood pressure that reached hypertensive levels. These mechanisms are related to the ability of ND to produce a reduction of the anti-inflammatory cytokine (IL-10) and augmentation of the pro-inflammatory cytokines (IL-6 and TNF-a) causing cardiac remodeling and injury [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these changes, animals treated with ND demonstrated increased blood pressure that reached hypertensive levels. These mechanisms are related to the ability of ND to produce a reduction of the anti-inflammatory cytokine (IL-10) and augmentation of the pro-inflammatory cytokines (IL-6 and TNF-a) causing cardiac remodeling and injury [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Wei et al reported that plasma levels of IL-6, IL-8, and IL-10 at 5 minutes after crossclamp release correlated with myocardial injury, indicated by creatine kinase-MB levels at 6 hours. 7 We previously have found that elevated plasma levels of IL-6, IL-8, and IL-10 at 4 hours after reperfusion in lung transplantation correlated with progressive injury in the recipient allograft. 8 Thus, the early biomarker profile can identify patients more likely to progress to clinically apparent organ injury.…”
Section: Discussionmentioning
confidence: 90%
“…6 A correlation between the magnitude of cytokine response and severity of myocardial injury has been demonstrated. 7 In lung transplant patients, it has been shown that the magnitude of the early inflammatory response is associated with the severity of lung injury following transplantation. 8 Multiplex cytokine assays now allow measurement of 22 biomarkers simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that systemic inflammatory response plays a major role in perioperative complications. Interleukin (IL)-1b, IL-6, IL-8, and tumor necrosis factor-α (TNF-α) are produced in the acute phase of the inflammatory response, and high-sensitivity C-reactive protein (hs-CRP) has been shown to correlate with multi-organ failure [8,9,10]. We aimed to investigate the changes in renal function after on- and off-pump CABG and their association with hs-CRP and TNF-α for the first time.…”
Section: Introductionmentioning
confidence: 99%